Humility, Intellectual Humility, and Subjective Well-Being: The Mediating Role of Altruistic Attitudes and Prosocialness: Kerendahan Hati, Kerendahan Hati Intelektual, dan Kesejahteraan Subjektif: Peran Mediasi Sikap Altruistik dan Prososial - Fahmi, Abu Bakar (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
Previous studies have explored the relationship between humility and subjective well-being, but have given limited attention to the correlation between cognitive aspect of humility, known as intellectual humility, and subjective well-being. Understanding the underlying mechanisms that drive this relationship is essential. Therefore, this study aimed to investigate the relationship between humility, intellectual humility, and subjective well-being, with a focus on whether altruistic attitudes and prosocialness mediated the relationship. An online questionnaire was administered to a total of 231 participants to assess their levels for these variables. The results showed that prosocialness mediated the relationship between humility, intellectual humility, and subjective well-being. However, the hypothesized mediation effect of altruistic attitudes was not supported. In conclusion, the results indicated that high levels of humility and intellectual humility in an individual could increase prosocialness, which in turn, enhanced subjective well-being.